UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING - Umi Supraptinah (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
This study aims to determine: (1) How the application of Problem Based Learning (PBL) model can improve mathematical problem solving abilities, (2) The extent to which the application of PBL model can improve mathematical problem solving abilities, and (3) How much PBL model can improve learning outcomes of mathematics. The research subjects are students of class VIIIF even semester, SMPN 1 Masaran at the academic year of 2016/2017. This research was held for 5 months, starting from January to May 2017. The research is a classroom action research consisting of 2 cycles. Each cycle consist of: planning, operating, observation, and reflection. Data analysis was carried out using qualitative descriptive techniques. The results of the research are: (1) PBL model can improve mathematical problem solving ability if the teacher is master and apply well based on steps: student orientation on problems, diagnosing problems, conducting individual or group investigations, developing and presenting the results of problem solving , and evaluation, (2) The application of PBL models can improve students' mathematical problem solving ability by 7.52% from 55.64% at the end of the first cycle to 63.16% at the end of the second cycle, (3) The application of PBL models can improve results learning aspects of understanding concepts, namely the average value of students' daily replay increased by 10.86% from 73.76% at the end of the first cycle to 84.62% at the end of the second cycle and the completeness of student learning increased by 22.58% from 64.52% end of first cycle increased to 87.10% at the end of the second cycle.